Abstract 17155: Lipoprotein (a) Testing in an Academic Medical System - Hamed, Marwan; Sherafati, Alborz; Alhalabi, Lubna; Naderian, Mohammadreza; Teymourzadeh, Azin; Saadatagah, Seyedmohammad; Nur, Yakub; Kullo, Iftikhar J (Circulation (New York, N.Y.), 2023)
Introduction: Lp(a) is a causal risk factor for ASCVD that is often elevated in patients with personal or family history (FHx) of ASCVD. The 2019 ESC guidelines recommend universal Lp(a) testing, while the 2019 AHA/ACC guidelines include Lp(a) as a 'risk enhancer'. We used electronic health records (EHR) to assess utilization of Lp(a) testing in patients with ASCVD, premature ASCVD, and FHx of ASCVD at Mayo Clinic sites in Rochester MN, Phoenix AZ and Jacksonville FL and the Mayo Clinic Health System (MCHS) from 1999-2021. Methods: We ascertained Lp(a) testing using LOINC codes and ASCVD status using validated ICD/CPT-based algorithms. ASCVD included coronary heart disease (CHD), cerebrovascular disease (CVD) (ischemic stroke and/or carotid artery stenosis), peripheral artery disease, and abdominal aortic aneurysm. Premature ASCVD was defined as occurring in males < 55 years and females < 65 years. We ascertained FHx using EHR survey data from 2017-2021. We estimated the proportion of patients with ASCVD, premature ASCVD, or FHx of ASCVD who underwent Lp(a) testing. Results: Between 1999-2021, we identified 310,760 patients with at least 1 ASCVD subtype of whom 66,710 had premature disease. FHx data was available starting 2017. For the timeframe 2017-2021, we identified 267,177 patients with FHx of ASCVD and 90,269 ASCVD patients. As summarized in Table 1, Lp(a) was tested only in a small proportion of patients; 7% of ASCVD patients, 11% of premature ASCVD patients, and 6% of patients with FHx of ASCVD. Premature CHD patients had the highest testing proportion (17%). Conclusions: Our results demonstrate underutilization of Lp(a) testing in patients with personal or FHx of ASCVD. Lp(a) is one of the mediators of "ASCVD residual risk" in patients on statins, and with new Lp(a)-lowering medications in phase III clinical trials, patient and provider education will be needed to increase awareness of Lp(a) as a modulator of ASCVD risk.